POTENSI IMPLEMENTASI TEKNOLOGI BLOCKCHAIN DALAM SISTEM INFORMASI AKUNTANSI PEMERINTAHAN DI INDONESIA - Dhiyaulhayi Al-Lust, Ilma; Tri Setyorini, Cristina (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2025)
Blockchain technology has been widely adopted in various sectors in this modern era. However, its application in accounting information systems in the government sector, especially in Indonesia, is still relatively limited. This research aims to explore the potential that can be generated through the implementation of blockchain in accounting information systems in government. Using a qualitative method based on a literature review, this research found that the implementation of blockchain can provide three main benefits: increasing the government's credibility in the eyes of the public, reducing the risk of manipulation and fraud, and increasing overall operational efficiency. The limitation of this research is the use of a limited approach to literature reviews. It is hoped that further research can explore this topic in more depth through quantitative and qualitative methods, including in-depth interviews to gain more holistic insights.